2004
DOI: 10.1524/ract.92.9.671.55012
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and geochemical association of actinides in a contaminated soil as a function of grain size

Abstract: The distribution of actinides in a contaminated soil as a function of grain size was investigated by determining 239,240 Pu, 241 Am, and 238 U after size fractionation. The soil was contaminated as the result of a fire at a nuclear missile site in the US. In all cases, the activity of each isotope increased with decreasing particle size, although differences were observed for 238 U. A simple spherical model was used to represent surface area as a function of grain size. Fitted values for the distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The U concentration increased by 6.6% after removal of Fe and Mn oxides,376showing that there is little or no U in the removed phase. A similar observation was reported 377 byLee et al (2004), while leaching soil samples with ammonium acetate. When the leaching 378 procedure was complete 0.9% of U was removed from the sample.379When the clay-size fraction was subsequently removed from the leached sample, U380 concentration decreased by 17% compared with the previous stage, indicating the presence of 381 a large proportion of U in the size fraction below 2 µm.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The U concentration increased by 6.6% after removal of Fe and Mn oxides,376showing that there is little or no U in the removed phase. A similar observation was reported 377 byLee et al (2004), while leaching soil samples with ammonium acetate. When the leaching 378 procedure was complete 0.9% of U was removed from the sample.379When the clay-size fraction was subsequently removed from the leached sample, U380 concentration decreased by 17% compared with the previous stage, indicating the presence of 381 a large proportion of U in the size fraction below 2 µm.…”
supporting
confidence: 87%
“…Removal of a fraction with a 450higher ( 230 Th/ 238 U) than the equilibrium value will leave the residue with a ( 230 Th/ 238 U) of < 451 1, and the same was observed here. Removing the clay-sized fraction from the residue again 452 increased the ( 230 Th/ 238 U), indicating that the ratio in the removed fraction is lower than the 453 residue from the previous step.454In summary, when the sequential extraction procedure for removal of different phases 455 is applied to a soil sample with little or no secondary phases, the U-series isotope ratios vary 456 in a similar way to that observed with soil/sediment samples containing secondary phases 457(Blanco et al, 2004;Lee et al, 2004;Schultz et al, 1998;Plater et al, 1992).…”
mentioning
confidence: 82%
“…Lee et al (2004) indicated that Pu tended to partition to specific soil particles rather than to sorb homogeneously to all particles. As shown in Table 1 and Fig.…”
Section: þ240 Pu Activities and 240 Pu/ 239 Pu Atom Ratios In Surfmentioning
confidence: 99%
“…However, for the various size fractions of the BOMARC soil, the calculated value of 241 Am (AAm ) 1.81 Bq/g) was a little higher than the measured activity concentration of 241 Am (1.08 Bq/g) ( Figure 3). These results suggest that the 241 Am produced from 241 Pu decay is less refractory (19) …”
Section: Resultsmentioning
confidence: 87%